Coefficient estimates for starlike and convex functions related to sigmoid functions - Raza, M.; Thomas, D. K.; Riaz, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5We give sharp coefficient bounds for starlike and convex functions related to modified sigmoid functions. We also provide some sharp coefficients bounds for the inverse  functions and sharp bounds for the initial logarithmic coefficients and  some coefficient differences.